Renegosiasi sebagai Upaya Penyelesaian Wanprestasi dalam Kontrak Bisnis Selama Masa Pandemi Covid-19 - Aryabang Bang Frisyudha; I Nyoman Putu Budiartha; Ni Komang Arini Styawati (Warmadewa Press, 2021)
Government policies due to the spread of Covid-19 have caused a weakening economic impact due to restrictions on community activities as well as business activities including the implementation of business contracts. The realizing of the rights and obligations of the business contract is hampered, and even there is the possibility that it will not be carried out which caused non-performance of contract. One of the contracts that caused it during the pandemic is the banking sector which refers to credit contracts. The research method used is normative research with statutory and approach. The technique of collecting materials applied in this research is literature study in the form of literature, journals and the results of previous research and documentary studies. in the form of a collection of the documents with interpretation and review through statutory regulations based on primary and secondary legal sources. The results shows that the legal consequences of renegotiation on the implementation of business contracts during the Covid-19 pandemic have generated goodwill from the parties in the contract where both parties act with consideration of the interests of the other party as well as during the current pandemic where creditors must pay attention to the interests of the debtor and the role The government in its efforts to settle business contract defaults during the pandemic is to implement a countercyclical policy.